Comparative Study of Epidural Block with Combined Femoral and Sciatic Nerve Block in Adults for Lower Limb Surgery using Bupivacaine with Fentanyl - Gulia, Abhity; Kohli, Pramod; Pandey, Maitree (Journal of Anaesthesia and Pain, 2024)
Background: Combined femoral and sciatic nerve blocks for lower limb surgery have been shown to be as effective as epidural blocks for intraoperative anesthesia and postoperative analgesia. This study compared the analgesic effect of epidural and the combined femoral and sciatic nerve block for lower limb surgeries in adults.Methods: This randomized controlled study included 60 patients who underwent lower limb surgery, divided into two groups to receive epidural (Group E, n = 30) or combined femoral and sciatic nerve block (Group PNB, n = 30). The duration of sensory and motor block, intraoperative hemodynamics, duration of postoperative analgesia, and adverse effects were assessed. Data was analyzed using McNemar’s test with α = 0.05.Result: There are no intraoperative hemodynamic changes in group PNB. The sensory block lasted 18.81 ± 1.78 hours, and postoperative analgesia for 17 ± 1.87 hours in group PNB. Whereas in group E, the sensory blockade lasted for 6.54 ± 0.87 hours and postoperative analgesia for 5.13 ± 1.13 hours (p = 0.000). The duration of the motor blockade in group E was 4.48 ± 1.02 hours. No motor blockade was seen in group PNB. No nausea, vomiting, hypotension, numbness, or urine retention were noted in group PNB. In group E, hypotension was noted at 15, 30, and 45 minutes, with 33.3% having nausea and 13.3% postoperative vomiting.Conclusion: Femoral and sciatic nerve block provide similar surgical conditions for lower limb surgeries with better hemodynamic stability, earlier ambulation, and longer duration of postoperative analgesia than epidural.